Democratization and the role of political parties in the electoral system of the Republic of Kazakhstan - Amandykova, S.K.; Ibraeva , N.A. (Bulletin of the Karaganda University “Law Series”, 2021)
The article examines the role of political parties at all stages of the electoral process, analyzing political parties as an institution of civil society and their interaction with the state authorities. A study of political parties from the point of view of multiparty and pluralism is conducted. In addition, the work analyzes the legislative acts in the field of electoral law that regulate the organization and activities of political parties. Based on the research and analysis of foreign legislation in the field of elections, the authors put forward their own vision of Article one of the Law of the Republic of Kazakhstan “On Political Parties”, analyze the status of political parties at the legislative level. The authors also consider the requirements for political parties in the field of elections, conduct a legal analysis of the proportional electoral system, and analyze the issues of reducing the entry barrier. The multiparty system as a sign of democratization of society gives rise to disputes, in this regard the article examines the legal regulation of the status of political parties in the Parliament, provides a brief description of legislation that would extend the powers and rights of the parties representing the opposition in Parliament. The purpose of the article is to determine the role of political parties in the electoral process and further improve the legislation in the field of electoral law. In this regard, based on the analysis of monographic studies of periodical literature and normative legal acts, specific proposals were put forward to improve and further determine the legal status of political parties.